Description of five new species of Epitola sensu lato (Lepidoptera: Lycaenidae: Poritiinae) from West and Central Africa - Sáfián, Szabolcs; Collins, Steve; Warren-Gash, Haydon; Belcastro, Claudio (Zootaxa, 2021)
Five new species of Epitola s.l. (Lycaenidae: Poritiinae) are described in the genera Stempfferia Jackson, 1962 and Cephetola Libert, 1999. Stempfferia salonga sp. n. was found in the ‘Cuvette Centrale’ of the Democratic Republic of Congo and a single specimen was identified also from southern Cameroon. The similar S. buea sp. n. is known only from the unique holotype collected at the foothills of Mount Cameroon, while S. michelliberti sp. n. is distributed in lowland rainforest between southeast Ivory Coast and Guinea. The new species of Cephetola were found only in Liberia. Cephetola praecox sp. n. is known from a single upland forest locality in the Putu Range, whereas C. wologizi sp. n. was collected also in upland forest in the Wologizi Mountains.